TRANSCRIPTOMIC APPLICATION TO UNDERSTAND THE EXPRESSION PROFILE OF ETHYLENE RESPONSIVE FACTOR (ERF) DURING BANANA RIPENING IN A AND B GENOME - Dewi Nirmala Sari, Lutfi
Banana as climacteric fleshy fruit was characterized by an increase in ethylene autocatalytic production and respiratory during ripening. As ancestors of the modern cultivated banana, Musa acuminata (genome A) and Musa balbisiana (genome B) show different profile of ripening process. During relatively short postharvest period, banana fruit undergoes delicate changes to its metabolic and physiological traits through well-organized syncronization of plant hormones and regulatory steps. The involvement of ethylene hormone and ethylene response factor (ERF) transcription factor (TF) in the transcriptional regulation of ethylene biosynthesis genes during ripening remains largely unclear. A clear understanding of these hormone and regulatory genes is crucial for extending the banana shelf life. Banana were harvested and monitored during both natural and ethylene-induced ripening processes. Assesment of color change, peel:pulp ratio, total soluble solids (TSS), and starch conversion showed different profiles between ethylene-treated and non-treated fruits on Musa acuminata cv. Cavendish or Musa balbisiana cv. Klutuk. In this study, transcriptional changes of ERF genes were investigated using RNA-seq technology on unripe (day 1) and ripe (day 7) of Musa acuminata cv. Cavendish. Results revealed 1.379 and 1.577 differentially expressed genes (DEGs) in the unripe and ripe stage samples, respectively. DEGs were subjected to Gene Ontology analysis and 41 categories were significantly enriched in the groups ‘cellular components’, ‘biological process’, and ‘molecular functions’. Several ERF transcription factors were differentially expressed between unripe and ripe banana fruits. Selected ERFs (MaERF083 (Ma08_g33940) and MaERF026 (Ma10_g19470)) were subjected to gene expression analysis using quantitative RT-PCR (qRT-PCR) on banana genome A and genome B. Our physiological data and gene expression analysis shows that in addition to ethylene, that were significant difference ripening profiles between Musa acuminata cv Cavendish and Musa balbisiana cv. Klutuk. This indicates that both of cultivars have different sensitivity and response to ethylene treatment which may caused by different trancriptional regulation.